Starving Spanish families: need greater than ever (reprint) - Stevenson, Daniel M., Sir
042-0033-001 Reprinted from THE MANCHESTER GUARDIAN SATURDAY, FEBRUARY 25, 1939. STARVING SPANISH FAMILIES Need Greater Than Ever To the Editor of the Manchester Guardian Sir. — In the confident hope that the generous British public would wish to share its Christmas cheer with the poor sufferers in Spain, particularly in the densely populated sector in and around Madrid, arrangements were made by the Scottish Ambulance Unit to send out in November and December consignments of foodstuffs, medical stores, and comforts at a total cost exceeding £4,000. Unfortunately, so many other urgent claims had to be dealt with at the same time - China, Czecho-Slovakia, German and Jewish refugees — that the unit's share of public benevolence fell far short of our liabilities, so much so that our deficit is still nearly £3.000 To this must be added the cost of further shipments for which Miss Jacobsen, the commandant, is asking at frequent intervals. The total cost of them would exceed £2.000, at least half of which is desperately needed to enable the staff to deal satisfactorily with urgent cases among the families — over 1,000 — on her special list. As I pointed out in a previous letter, " family " in Spain does not mean merely a household of half a dozen, but often includes uncles, aunts, grandparents, and more distant relatives, numbering in some cases fifteen to thirty. The Scottish Ambulance Unit has a magnificent record. It was the first in the field, our ambulances having been at actual work in the Madrid sector in September 1936, after a journey of some two thousand miles overland from Glasgow. We are proud of what it has done and of the splendid recognition it has received not only from the British press but from all the leading newspapers of Spain. Our expenditure so far has been £20,347, of which £2,206 has had to be borrowed. The generous public has contributed the balance in sums varying from one of £1,000, one of £200, several of £100, still more of £50, £25, £20, £10, £5, and £1, plus a very large number of smaller sums down to single shillings, some of the smallest being obviously sent at great personal sacrifice. All are welcome, however small, but this time we hope that our well-to-do friends will make a special effort and enable us to say that we are free from debt and able to face another £1,000 shipment. May I add a special appeal to those of your readers who have not seen their way to help because of personal views on the war ? This is hardly fair to us; ever since our staff landed in Spain they have been instructed to give help and succour where most needed, irrespective of party or politics. Many people are saying, " Further help is unnecessary: the end of the war is in sight." All must hope that the dreadful slaughter is at an end, but, alas! not so the starvation. The need is greater than ever and cannot but continue for months. Donations addressed Sir Daniel Stevenson, Cleveden, Glasgow, will be gratefully acknowledged. — Yours, &c. D.M. Stevenson. Glasgow. February 23. 292/946/42/33